Unlocking Potential : How ICT can Support Children with Special Needs - McKeown, Sally (Birmingham Questions Publishing Company, 2000)
Illustrates how computer technology can be of benefit to children with communication problems and other special needs. A valuable reference for teachers, special needs assistants and carers.
Include Illustrations and Sources.
How ICT can Support Children with Special Needs.
Keywords: Educational technology -- Special education--Data processing -- Children with disabilities--Education--Data processing